LEVON SHAGHOIAN'S ROLE IN SAVING THE VAN-VASPOURAKAN REFUGEES (MARCH-AUGUST 1918) - Ohanyan, Seda (Armenian Folia Anglistika, 2025)
The activities of several heroes, who dedicated their lives to the Armenian national liberation struggle in the twentieth century, remain unknown or have not been thoroughly studied for various reasons. Among those individuals who dedicated themselves entirely to the national struggle for survival was Levon “Pasha” Shaghoian. It is noteworthy that in the course of history, there have often been individual leaders who either played a fateful role in the survival and development of their nation or, on the contrary, were the cause of their own people’s demise and its subsequent disappearance from the pages of history. Although Levon Shaghoian was not a talkative person, he left us with extensive written records of his writing. Therefore, the notes, memoirs, and articles of his collaborators served as the basis for reflecting on his activities in the Fatherland. The primary sources for this article are archival materials from the National Archives of Armenia, the personal archive of Levon Shaghoian, and the Brief History of the Iraqi-Armenian Diocese. The official central archives of the ARF in Boston, as well as the memoirs of participants in the region's self-defense activities, have also been considered.
Keywords: WW1; Armenian Genocide; Levon Shaghoian; Armenian refugees; Western Armenia; Cilicia; Iraqi-Armenian diocese; Van-Vaspourakan